Comparative LCA of automotive gear hobbing processes with flood lubrication and MQL - Soares, Luiz Arthur Paluch; Firmino, Alessandro Silveira; de Oliveira, José Augusto [UNESP]; Silva, Diogo Aparecido Lopes; Saavedra, Yovana María Barrera; da Silva Moris, Virginia Aparecida (Springer Nature, 2022)
The life cycle inventory (LCI) data of a gear hobbing was obtained by means of the methodology unit process life cycle inventory (UPLCI), to conduct a comparative life cycle assessment (LCA) between hobbing assisted by flood lubrication (FL) and minimum quantity lubrication (MQL). The results pointed out 4 among 11 normalized environmental impact categories totalized more than 80% of the accumulated impacts: Fossil Depletion (43%), Climate Changes (19%), Terrestrial Acidification (11%), and Freshwater Consumption (8%). The identified hotspot in the case study was the input flow of raw material for the system “Hobbing Machine,” which was linked to more than 75% of the total amount of normalized potential environmental impacts. Once, changes on raw material depends on the gear design, the research focused on the environmental aspects of energy and cutting fluid consumption, which depends directly on the hobbing process parameters. The introduction of MQL provided reduction of 70.77% on the total amount of normalized potential impacts, while the strategies to reduce electric energy consumption by the machine tool accounted only for 3.74%. Nevertheless, when raw material flow is considered in the LCA, it turns into the process hotspot, due to high energy demanded in the steel-making process, forging, and turning operations to shape the semi-finished gear. The relevance of the key environmental aspects, electric energy, cutting fluids, and raw material, can vary significantly according to the gear size itself. The performed case study was considered a pilot project for the hosting company and can be scaled up to a whole gear manufacturing plant to identify manufacturing cells, which are eligible to optimization in the use of cutting fluids and electric energy by the machine tools.
Keywords: Gear hobbing; Green manufacturing; Minimum quantity lubrication; Unit process life cycle inventory